2019
DOI: 10.1001/jamanetworkopen.2019.0595
|View full text |Cite
|
Sign up to set email alerts
|

Association of Methadone Treatment With Substance-Related Hospital Admissions Among a Population in Canada With a History of Criminal Convictions

Abstract: Key Points Question Is adherence to methadone associated with a lower risk of hospital admission among individuals with criminal convictions? Findings In this cohort study including 11 401 Canadian individuals, periods during which methadone was dispensed were associated with lower rates of any acute hospital admission. Meaning Adherence to methadone among individuals with criminal convictions may contribute to lower rates of acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 71 publications
(117 reference statements)
0
17
0
Order By: Relevance
“…2,3 Populations involved in the criminal legal system (e.g., in prison, in jail, on parole, on probation, in a specialty court, or formerly incarcerated) also benefit from MOUD, with evidence of reduced opioid use, hospital admissions, incarceration, arrests, and violent and non-violent offenses. [4][5][6][7][8][9][10] Among people exiting prison, MOUD reduces reincarceration risk 11 and is cost-effective. 12 Despite evidence on its effectiveness, veterans exiting prison have lower utilization rates of MOUD at Veterans Health Administration (VHA) facilities than veterans not involved in the legal system.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Populations involved in the criminal legal system (e.g., in prison, in jail, on parole, on probation, in a specialty court, or formerly incarcerated) also benefit from MOUD, with evidence of reduced opioid use, hospital admissions, incarceration, arrests, and violent and non-violent offenses. [4][5][6][7][8][9][10] Among people exiting prison, MOUD reduces reincarceration risk 11 and is cost-effective. 12 Despite evidence on its effectiveness, veterans exiting prison have lower utilization rates of MOUD at Veterans Health Administration (VHA) facilities than veterans not involved in the legal system.…”
Section: Introductionmentioning
confidence: 99%
“…There is clear evidence supporting a correlation between Canada's first line OAT agents, MMT and BUP, and improved mental health. The study by Russolillo et al (2019) demonstrates that there is a substantial risk reduction for mental health related hospitalization associated with MMT therapy. Russolillo et al (2019) also demonstrated that the benefit of MMT was dose dependent.…”
Section: Improved Mental Healthmentioning
confidence: 98%
“…The study by Russolillo et al (2019) demonstrates that there is a substantial risk reduction for mental health related hospitalization associated with MMT therapy. Russolillo et al (2019) also demonstrated that the benefit of MMT was dose dependent. As with physical health improvements, Russolillo et al…”
Section: Improved Mental Healthmentioning
confidence: 98%
See 2 more Smart Citations